2011
DOI: 10.1002/jobm.201100077
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity during Rotary Drum and Windrow Pile composting

Abstract: This study investigates the prevailing microbial communities during the composting of vegetable waste, cattle manure and saw dust, in a household (250 l) batch scale Rotary Drum composter and Windrow Pile. Physico-chemical parameters were analyzed to study the organic matter transformations. Total organic matter reduced from 63.8% to 36.2% in rotary drum and 39.6% in windrow pile composting. The C/N ratio decreased from 26.52 to 8.89 and 14.33 in rotary drum and windrow pile composting. The indigenous populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 18 publications
3
17
1
1
Order By: Relevance
“…This was the highest reduction among all other trials. However, it has also been reported that fungal count had reduced completely in vegetable waste composting (Bhatia et al 2012). During municipal solid waste composting fungal count decreased from 4.5 × 10 6 CFU/g to 6.3 × 10 3 CFU/g in the 3…”
Section: Analysis Of Microbial Communitymentioning
confidence: 95%
See 2 more Smart Citations
“…This was the highest reduction among all other trials. However, it has also been reported that fungal count had reduced completely in vegetable waste composting (Bhatia et al 2012). During municipal solid waste composting fungal count decreased from 4.5 × 10 6 CFU/g to 6.3 × 10 3 CFU/g in the 3…”
Section: Analysis Of Microbial Communitymentioning
confidence: 95%
“…The microbial communities in whole composting period keep on changing (Hassen et al 2001;Bhatia et al 2012). Bacteria, actinomycetes, streptomycetes and fungi are the major contributors of biodegradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final residual organic matter consisted of humic-like substances which are highly non-biodegradable and also the most stable fraction of mature compost (Chefetz et al 1996). In composting, the organic matter degradation is carried out by different diversity of microorganisms including mesophilic bacteria, spore-forming bacteria, fungi and actinomycetes to transform them into stable humic components (Garcia et al 1992;Bhatia et al 2012). However, the degradation pattern and humification during composting is considered to follow different pattern depending on the raw materials used for composting (Huang et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…And moreover, the final compost had been completely stabilized with lower carbon dioxide (CO 2 ) evolution and oxygen uptake rate (OUR). Organic fractions of MSW, vegetable waste, water hyacinth and many other wastes had been successfully composted using rotary drum composter (Tolvanen et al 2005;Bhatia et al 2012;Singh and Kalamdhad 2013). In addition, Gajalakshmi and Abbasi (2008) have also reported the possible advantages of composting and the use of rotary drum for effective degradation process.…”
Section: Introductionmentioning
confidence: 99%